MAX-DOAS measurements of NO2, HCHO and CHOCHO at a rural site in Southern China - Xin Li; Brauers, Theo; Hofzumahaus, Andreas; Lu, Keding; Li, Y. P.; Min Shao; Wagner, T.; Wahner, Andreas (Atmospheric Chemistry and Physics, 2013)
We performed MAX-DOAS measurements during the PRIDE-PRD2006 campaign in the Pearl River Delta region (PRD), China, for 4 weeks in July 2006 at a site located 60 km north of Guangzhou. The vertical distributions of NO2, HCHO, and CHOCHO were independently retrieved by an automated iteration method. The NO2 mixing ratios measured by MAX-DOAS showed reasonable agreement with the simultaneous, ground based in-situ data. The tropospheric NO2 vertical column densities (VCDs) observed by OMI on board EOS-Aura satellite were higher than with those by MAX-DOAS. The 3-D chemical transport model CMAQ overestimated the NO2 VCDs as well as the surface concentrations by about 65 %. From this observation, a reduction of NOx emission strength in CMAQ seems to be necessary in order to well reproduce the NO2 observations. The average mixing ratios of HCHO and CHOCHO were 7 ppb and 0.4 ppb, respectively, higher than in other rural or semirural environments. The high ratio of 0.062 between CHOCHO and HCHO corresponds to the high VOCs reactivity and high HOx turnover rate consistent with other observations during the campaign.